Biochar can mitigate methane emissions by improving methanotrophs for prolonged period in fertilized paddy soils. (October 2019) - Wu, Zhen; Song, Yanfeng; Shen, Haojie; Jiang, Xueyang; Li, Bo; Xiong, Zhengqin
Abstract: Biochar application to fertilized paddy soils has been recommended as an effective countermeasure to mitigate methane (CH4 ) emissions, but its mechanism and effective duration has not yet been adequately elucidated. A laboratory incubation experiment was performed to gain insight into the combined effects of fresh and six-year aged biochar on potential methane oxidation (PMO) in paddy soils with ammonium or nitrate-amendment. Results showed that both ammonium and nitrate were essential for CH4 oxidation though high ammonium (4 mM) inhibited PMO as compared to low ammonium (1 mM and 2 mM), and that nitrate was better in promoting PMO than ammonium. Moreover, ammonium-amendment promoted type I pmoA, and nitrate-amendment enhanced type II pmoA abundance. Both fresh and aged biochar increased PMO as well as nitrification by enhancing the total, type I and type II methanotrophs as compared to the control. Increased soil PMO with mineral N input in both six-year aged biochar and fresh biochar amendment, indicating that biochar mitigated CH4 by promoting PMO for prolonged period in fertilized paddy soils. Graphical abstract: Image 1 Highlights: Ammonium & nitrate benefited potential CH4 oxidation with greater extent from nitrate. Ammonium promoted type I, while nitrate promoted type II methanotrophs. Biochar increased CH4 oxidation by alleviating inhibitory effect of ammonium. Biochar amendment promoted CH4 oxidation for prolonged period.